(untitled) (International Journal of Engineering and Computer Science, 2017)
When the network environment is defined then some physical properties of network are set such as propagation type, spectrum type etc. These properties control the network communication. This propagation method deals with the channel selection, channel sensing and to perform the effective communication over the network. There are number of constraints that affect the communication over a network. To achieve the effective output from the network, it is required to define network under defined constraints. These all constraint depends on type of network, its topology and the type of communication performed in that network. The presented work is focused on the communication analysis for an indoor mobile network. This is an adhoc network that is limited to a small area such as a room or the building. The network is congested having a small range of communication for each node. In such network, the communication strength depends on the propagation type used in the network. There are number of such propagation methods to provide effective communication over the network. To achieve the effective communication, an effective propagation must be selected for the communication. These propagation methods also affected from different network, environmental and communication parameters. To optimize the indoor communication network by setting up some channel specific constraints under different parameters. The work is about to perform the effective deployment in case of channel noise and disruption analysis. The presented work will be performed on three different models, they are: ray-leigh indoor propagation model,friis model,log distance shadowing model. The work is about to reduce the BER while performing the communication in indoor network under different distance and density constraints.